Analysing of Cat Zoosemy in the Uzbek and English Works - Sobirovna, Toirova Umida (International Journal on Orange Technologies, 2022)
This article analyses the term of zoosemy through cat characters. The character of cat will discuss with different ways and meaning in Uzbek and English literature. The symbol of cat perfectly have used in both literary works. Each meaning and symbol has their own features that after knowing the zoosemy of cat in Uzbek and English literature every person realizes on writers using their symbols skillfully. Not only using the cat in their works but also using some simile or allegory can help to comprehend the term of zoosemy through description. This section includes cat zoosemy via character, physical appearance, behavior and allegorical meaning, various ideas of different genres and usage of cat in both Uzbek and English literature can help readers to differentiate the character of cat.